Changes in Skeletal Muscle PAK1 Levels Regulate Tissue Crosstalk to Impact Whole Body Glucose Homeostasis - Merz, Karla E.; Tunduguru, Ragadeepthi; Ahn, Miwon; Salunkhe, Vishal A.; Veluthakal, Rajakrishnan; Hwang, Jinhee; Bhattacharya, Supriyo; McCown, Erika M.; Garcia, Pablo A.; Zhou, Chunxue; Oh, Eunjin; Yoder, Stephanie M.; et al. (Frontiers in Endocrinology, 2022)
Skeletal muscle accounts for ~80% of insulin-stimulated glucose uptake. The Group I p21–activated kinase 1 (PAK1) is required for the non-canonical insulin-stimulated GLUT4 vesicle translocation in skeletal muscle cells. We found that the abundances of PAK1 protein and its downstream effector in muscle, ARPC1B, are significantly reduced in the skeletal muscle of humans with type 2 diabetes, compared to the non-diabetic controls, making skeletal muscle PAK1 a candidate regulator of glucose homeostasis. Although whole-body PAK1 knockout mice exhibit glucose intolerance and are insulin resistant, the contribution of skeletal muscle PAK1 in particular was unknown. As such, we developed inducible skeletal muscle-specific PAK1 knockout (skmPAK1-iKO) and overexpression (skmPAK1-iOE) mouse models to evaluate the role of PAK1 in skeletal muscle insulin sensitivity and glucose homeostasis. Using intraperitoneal glucose tolerance and insulin tolerance testing, we found that skeletal muscle PAK1 is required for maintaining whole body glucose homeostasis. Moreover, PAK1 enrichment in GLUT4-myc-L6 myoblasts preserves normal insulin-stimulated GLUT4 translocation under insulin resistance conditions. Unexpectedly, skmPAK1-iKO also showed aberrant plasma insulin levels following a glucose challenge. By applying conditioned media from PAK1-enriched myotubes or myoblasts to β-cells in culture, we established that a muscle-derived circulating factor(s) could enhance β-cell function. Taken together, these data suggest that PAK1 levels in the skeletal muscle can regulate not only skeletal muscle insulin sensitivity, but can also engage in tissue crosstalk with pancreatic β-cells, unveiling a new molecular mechanism by which PAK1 regulates whole-body glucose homeostasis.